2015
DOI: 10.1523/eneuro.0076-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Single-Trial Event-Related Potential Correlates of Belief Updating

Abstract: Belief updating—the process by which an agent alters an internal model of its environment—is a core function of the CNS. Recent theory has proposed broad principles by which belief updating might operate, but more precise details of its implementation in the human brain remain unclear. In order to address this question, we studied how two components of the human event-related potential encoded different aspects of belief updating. Participants completed a novel perceptual learning task while electroencephalogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
58
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 55 publications
15
58
2
Order By: Relevance
“…These broad anatomical distinctions are in accordance with our findings if one assumes that frontal sources contribute to the generation of scalprecorded P3a waves and that parietal sources contribute to the generation of scalp-recorded P3b waves (Polich, 2007). The P3a finding needs further specification because previous ERP studies revealed an association between Bayesian updating and P3a amplitudes rather than between prior probabilities and P3a amplitudes (Bennett et al, 2015;Kolossa et al, 2015). The P3a waves in this study were more anteriorly distributed than the P3a waves in the previous studies, but this issue clearly needs to be further examined by future studies.…”
Section: The Current Study In the Context Of The Existing Literaturesupporting
confidence: 91%
See 1 more Smart Citation
“…These broad anatomical distinctions are in accordance with our findings if one assumes that frontal sources contribute to the generation of scalprecorded P3a waves and that parietal sources contribute to the generation of scalp-recorded P3b waves (Polich, 2007). The P3a finding needs further specification because previous ERP studies revealed an association between Bayesian updating and P3a amplitudes rather than between prior probabilities and P3a amplitudes (Bennett et al, 2015;Kolossa et al, 2015). The P3a waves in this study were more anteriorly distributed than the P3a waves in the previous studies, but this issue clearly needs to be further examined by future studies.…”
Section: The Current Study In the Context Of The Existing Literaturesupporting
confidence: 91%
“…Kolossa, Fingscheidt, Wessel, and Kopp (2013) modeled the surprise-sensitivity of trial-by-trial P3b amplitude variations as originating from the operation of multiple digital filters in the brain (i.e., two parallel first-order infinite impulse response low-pass filters and an additional fourth-order finite impulse response high-pass filter). Kolossa, Kopp, and Fingscheidt (2015) replicated the surprise-sensitivity of P3b amplitude variations and showed that the anteriorly distributed P3a encodes Bayesian updating, a finding that was also reported by Bennett, Murawski, and Bode (2015).…”
Section: Overview Of the Existing Erp Researchsupporting
confidence: 67%
“…A simple Bayesian model provided dynamic estimates of the belief states of each participant on each trial, which allowed for trial‐by‐trial quantification of (a) the uncertainty of beliefs, and (b) the magnitude of belief updates. Importantly, these estimates of belief state were found to correlate with the amplitude of components of the ERP, including a positive relationship between P3 amplitudes and belief update magnitude that was not accounted for by simpler models (Bennett et al, ). This finding was consistent with earlier theories and other empirical findings linking the P3 and Bayesian belief updating (Kolossa et al, ; Kopp, ).…”
Section: Introductionmentioning
confidence: 96%
“…This suggests that discrepancies between Bayesian models and human behavior may be in part motivational: since full Bayesian inference can be computationally demanding, participants' motivation to engage in effortful cognition may moderate their use of strategies that resemble Bayesian belief updating (Lieder & Griffiths, ; Shenhav, Botvinick, & Cohen, ). Since an important factor that directly modulates motivation is the availability of reward, this motivational account predicts that the use of monetary performance incentives in learning tasks (as in the study by Bennett et al, ) may affect the behavioral strategies employed by participants. Monetary incentive has been linked with improved performance in various learning paradigms (e.g., Bonner & Sprinkle, ; Kleih, Nijboer, Halder, & Kübler, ), but the effect of monetary incentives on participants' use of Bayesian belief updating is an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, we estimated the normalized entropy of the individual histograms, according to Shannon's formula (Shannon, 1948; Shannon and Weaver, 1949; cf. also Bennett et al, 2015): left= - i=111true(pi × log2pitrue)log211  where p i is the relative frequency at bin i . The normalized entropy reflects the degree of belief uncertainty regarding the bag composition.…”
Section: Resultsmentioning
confidence: 99%